Extracts from The Cochrane Library: Coblation versus other surgical techniques for tonsillectomy (review) - Burton, M; Manning, S; Rosenfeld, R (2008)
"The Cochrane Corner" is a quarterly section in the Journal that highlights systematic reviews relevant to otolaryngology-head and neck surgery, with invited commentary to highlight implications for clinical decision making. This installment features a Cochrane Review titled "Coblation versus other surgical techniques for tonsillectomy," which concludes there is inadequate evidence to determine whether coblation tonsillectomy is better or worse than other methods of performing the procedure. © 2008 American Academy of Otolaryngology-Head and Neck Surgery Foundation.